Secondary endothelial keratoplasty: a narrative review of the outcomes of secondary corneal endothelial allografts - Moura-Coelho, Nuno (2021)
Background: We review the literature on the efficacy and safety outcomes of secondary Descemet stripping endothelial keratoplasty (DSEK) and Descemet membrane endothelial keratoplasty (DMEK). Methods: Literature search of English-written publications up to 27th September 2020 in PubMed database, using the terms "endothelial keratoplasty" in combination with keywords "secondary" or "repeat". In addition, we manually searched the references of the primary articles. Results: 27 studies (n = 651 eyes) were retained and reviewed, including 10 studies on repeat DSEK, 8 studies on repeat DMEK, 6 studies of DMEK following DSEK, and 3 studies of DSEK after failed DMEK. All studies reported significant improvement in visual acuity after secondary EK. Twelve studies compared visual outcomes between primary and secondary EK, reporting conflicting findings. Sixteen studies reported endothelial cell loss rates (%ECL) after secondary EK, and only one study reported significantly increased %ECL compared with primary EK. Allograft rejection episodes occurred in 1.8% of eyes (range 0-50%). Six studies compared complication rates between primary and secondary EK eyes, and only one study found a higher median number of complications. However, two studies reported higher regraft failure rates compared with primary EK eyes. Conclusions: Secondary EK is surgically feasible and renders significant visual improvement after failed primary EK, although it is not clear whether visual outcomes and allograft survival are comparable with primary EK, raising the question of whether secondary EK eyes are "low-risk" as primary EK eyes. Further larger, prospective studies are encouraged to obtain additional quality data on secondary corneal endothelial allotransplantation.